2003
DOI: 10.1124/jpet.103.057299
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Modeling of Abciximab Plasma Concentrations and ex Vivo Pharmacodynamics in Patients Undergoing Coronary Angioplasty

Abstract: An integrated structural pharmacokinetic/pharmacodynamic (PK/PD) model was developed for the glycoprotein IIb/IIIa antagonist abciximab administered to patients undergoing percutaneous transluminal coronary angioplasty. PK/PD data, in the form of plasma abciximab concentrations and ex vivo platelet aggregation in the presence of 20 M adenosine diphosphate, were obtained from two previously conducted clinical studies. Study 1 consisted of patients who were given abciximab as a single intravenous injection of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Consistently, we observed that the estimates for volumes of distribution of relatively potent small molecule HSP90 inhibitors were larger than those of less potent inhibitors when structurally similar compounds were compared in our drug discovery program. Since HSP90 is one of the most abundant proteins in unstressed eukaryotic cells, accounting for 1-2% of cytosolic protein (Parsell and Lindquist, 1993;Csermely et al, 1998), it may be possible that the target binding of HSP90 inhibitors affects in vivo PK profiles (e.g., TMDD) as is often observed for biologic drugs (Mager et al, 2003;Mager and Krzyzanski, 2005;Woo et al, 2007;Gibiansky and Gibiansky, 2009). As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistently, we observed that the estimates for volumes of distribution of relatively potent small molecule HSP90 inhibitors were larger than those of less potent inhibitors when structurally similar compounds were compared in our drug discovery program. Since HSP90 is one of the most abundant proteins in unstressed eukaryotic cells, accounting for 1-2% of cytosolic protein (Parsell and Lindquist, 1993;Csermely et al, 1998), it may be possible that the target binding of HSP90 inhibitors affects in vivo PK profiles (e.g., TMDD) as is often observed for biologic drugs (Mager et al, 2003;Mager and Krzyzanski, 2005;Woo et al, 2007;Gibiansky and Gibiansky, 2009). As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For HSP90 inhibitors, their bindings to pharmacological target are expected to be as rapid as many other biologics (Mager et al, 2003;Mager and Krzyzanski, 2005;Woo et al, 2007), and R total can be assumed to remain constant because of high HSP90 abundance accounting for 1-2% of the total proteins in normal cells (Parsell and Lindquist, 1993;Csermely et al, 1998). The internalization rate of HSP90 inhibitor-receptor complex can be assumed to be negligible because these inhibitors are considered to bind reversibly to the ATP-binding pocket of HSP90 in the cytosolic fraction without any elimination process through the formation of drug-receptor complex.…”
Section: Target-mediated Drug Disposition Of Hsp90 Inhibitors 1287mentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative rate of major adverse cardiac events was similarly reduced in the bolus-only arm (2.9%) and bolus + infusion arm (2.4%) as compared with placebo (5.3%) within the first 6 h after intervention [3]. However, higher rates of myocardial infarction and urgent target vessel revascularization were noted thereafter in the bolus arm as compared with bolus + infusion throughout 30 days [3].In the absence of concomitant P2Y 12 inhibition, withholding abciximab post-bolus infusion results in an approximately 30% drop in inhibition of platelet aggregation (IPA) at 6 h [1,4]. …”
mentioning
confidence: 99%
“…In the absence of concomitant P2Y 12 inhibition, withholding abciximab post-bolus infusion results in an approximately 30% drop in inhibition of platelet aggregation (IPA) at 6 h [1,4].…”
mentioning
confidence: 99%